Real Wages and the Demand for Skilled and Unskilled Male Labour in Ghana's Manufacturing Sector: 1991-1995. - Teal, F (CSAE (University of Oxford), 1997)
Real wage rates in Ghana have fallen substantially over the last twenty years. In this paper survey data for the years 1991–1996 is used to assess whether this fall has continued in the 1990s. It is shown that the fall in average real wage rates has continued, the relative wage of skilled labour has risen, the share of skilled wages in total wages has remained constant and the share of wages in value-added has risen. Factor share equations for skilled and unskilled labour are estimated which are consistent with the rise in skilled wages leading to substitution to unskilled labour and with technical regress raising the demand for unskilled labour. Real wage income in the sample has risen over the period.